Kultur Sekolah Sebagai Aplikasi Pendidikan Karakter: School Culture As Character Education Application - Jazaul Aufa; Nanang Qosim; Nur Fatimah (LP3M Universitas Islam Zainul Hasan Genggong, 2020)
The application of character education is currently only needed in schools, at home and in the community. Now these are not only early children, but also children in adulthood. The process of fostering student personality able to done in many ways, including them culture system of character education applications provided by the social environment that has a primary focus on shaping student character. School culture as an application of the formation of character among them is the character of religion, discipline, communicative, social care, patriotism, preparation and democracy.